Liquid–Liquid Interfacial Imaging Using Atomic Force Microscopy. Issue 16 (17th May 2017) - Costa, Luca; Li‐Destri, Giovanni; Pontoni, Diego; Konovalov, Oleg; Thomson, Neil H.
Abstract : Nanoscale imaging of a liquid/liquid interface by atomic force microscopy (AFM) is achieved through the self‐assembly of interfacial layers of either polymers, lipids, or nanoparticles. Stabilization of the interface through spreading of a thin film of polystyrene‐b‐poly(methyl‐methacrylate) block copolymer or 1, 2‐dioleoyl‐sn‐glycero‐3‐phosphoethanolamine lipids or adsorption of monolayers of silica nanoparticles allows reproducible imaging of these soft materials at an oil/water interface with nanoscale resolution on a timescale of 10 s. Amplitude modulation AFM is employed and requires that the subphase of water is below a critical depth of 100 µm to prevent excitation of gravity waves at the interface. The amplitude of these vertical oscillations is of the order of 1 nm but increases with the water layer depth. Below this critical water layer depth, force measurements show a linear compliance of the water/heptane and water/octane interfaces to be close to 10 −2 N m −1 . This study discusses in detail the experimental setup, sample preparation procedures, and AFM parameters necessary to achieve nanoscale resolution at the extremely soft and dynamic liquid interface. This expands the application of AFM to structural and dynamic nanoscale measurements for soft matter, biological, and nanomaterials away from solid supports. Abstract : A nanoscale resolved microscopy method to acquire in situ images of different material thin films assembled at liquid interfaces is introduced. The atomic force microscopy experimental approach is based on the minimization of naturally occurring gravity waves by reducing the liquid depth and the absence of large adhesion forces between tip and liquid by imaging liquid/liquid interfaces rather than air/liquid ones.